PENGARUH PEMBIAYAAN DANA MUDHARABAH DALAM MENSEJAHTERAKAN PARA NASABAH UMKM BERDASARKAN PRESPEKTIF MAQASHID SYARIAH - Hilmy Zein; Sri Herianingrum (Universitas Airlangga, 2019)
This study aims to examine the effect of mudharabah funding on the welfare of umkm customers based on Maqashid Syariah with variabel religion(ad-din), soul(an-nafs), sense(al-aql), offspring(an-nasl) and treasure(al-maal). The sample of this study is customers of mudharabah fund financing bank jatim syariah merr surabaya as many as 51 respondents. The data use are primary data collected using a questionnaire spread directly to customers umkm. Indicators of research variables are measured using likert scales 1 to 5. This research proves that mudharabah funding results have a significant positive effect on the welfare of customers based on maqashid sharia with religious variables religion(ad-din), soul(an-nafs), sense(al-aql) and treasure(al-maal), but on financing Mudharabah funds offspring variables (an-nasl) the results have a significant negative effect.Keywords: Mudharabah fund financing, Maqashid Syariah “ad-din, an-nafs, al-aql, an-nasl & al-maal.REFERENCESAscarya. 2007. Akad dan Produk Bank Syariah. Jakarta: PT Raja Grafindo Persada.Ali, Hamdani. 1986. FilsafatPendidikan. Yogyakarta: Kota KembangAntonio, Muhammad Syafi’i. 2001. Bank Syariah dari Teori ke Praktik. Jakarta: GemaInsani.Abdullah Saeed, Bank Islam dan Bunga: Studi Kritis Larangan Riba dan InterpretasiKontemporer, (Yogyakarta: Pustaka Pelajar, 2003), h. 91Hendi Suhendi, 2002, Fiqih Muamalah, Raja grafindo persada, Jakarta, hlm.136.http://jatim.bps.go.id/datastatistik/jawatimurkotasurabaya.434766, Diakses Pada 17 Febuari 2019. Http://ojk.go.id/id/kanal/iknb/Pages/Lembaga-Keuangansyariah, diakses pada 20 Januari 2019 Karim, Adiwarman. 2001. Ekonomi Islam, SuatuKajianKontemporer. Jakarta: GemaInsaniMujahidin, Akhmad, Ekonomi Islam: Sejarah, Konsep, Instrumen, Negara, dan Pasar,(Jakarta: Rajawali Pers, 2013), Cet- ke-2, h.257.Muhammad, Akuntansi Bank syariah,(Yogyakarta: Trust Media, 2009), h. 56Muhamad Syakir. 2004. Teknik PerhitunganBagi Hasil dan Profit Margin pada Bank Syariah. Yogyakarta: UII Press.Tadjab. 1994. PerbandinganPendidikan. Surabaya: KaryaAbditama.Todaro, Michael P. dan Stephen C. Smith.2003. Pembangunan Ekonomi di DuniaKetiga, edisikedelapan.Jakarta: Erlangga.Undang-Undang Republik Indonesia No. 20 tahun 2008 pasal 1 dan 6 tentang Usaha Mikro, Kecil dan Menengah.Undang-Undang Republik Indonesia No. 10 tahun 1998 tentang pengertian bank syariah.Undang-Undang Republik Indonesia No. 11 tahun 2009 tentang kesejahteraan sosial dan kesejahteraan UMKM.Undang-Undang Republik Indonesia No. 21 tahun 2008 tentang tugas lembaga keuangan syariah.Undang-Undang Nomor 1 Tahun 2013 tentang Lembaga Keuangan Mikro.